Regimes change and exchange rate dynamics : the rand - Mtonga, Elvis (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references (p. 186-206). === The rand has since the mid-1980s maintained a long swing of decline that reversed in 2002 for a brief while; resuming the swing shortly thereafter. In contrast to these fairly predictable fluctuations, the rand’s short run movements are increasingly volatile and seemingly unpredictable. Anchored in the asset approach to exchange rate determination, this study examines the two issues of the long run and short run exchange rate dynamics of the rand.